The whole motion : collected poems, 1945-1992 - Dickey, James (Wesleyan poetry., 1992)
For over three decades, James Dickey has been one of the nation's most important poets and a prominent man of letters. The Eagle's Mile, his most recent volume, was a triumphant success, a bold and innovative departure from his traditional verse. The New York Times declared, "Dickey continues to extend his vision as a major American poet," while Fred Chappell, himself a Bollingen Prize winner, wrote, "If there were a literary prize for Poetry That Has Shown Real Moxie, it ought to go to The Eagle's Mile."